MDM2/X Inhibitors as Radiosensitizers for Glioblastoma Targeted Therapy - Miles, Xanthene; Vandevoorde, Charlot; Hunter, Alistair; Bolcaen, Julie (Frontiers in Oncology, 2021)
Blocking the MDM2/X-p53 protein-protein interaction has been widely recognized as an attractive therapeutic strategy for the treatment of various cancers, including glioblastoma (GB). p53 is a multifunctional transcription factor that can be activated by cellular stresses, such as hypoxia and DNA damage. Upon activation, the tumor suppressor protein p53 responds to cellular damage by mediating cell cycle arrest, DNA repair and apoptosis. Hence, p53 activation plays a central role in cell survival and the effectiveness of cancer therapies. Alterations and reduced activity of p53 occur in 25-30 % of primary GB tumors, but this number increases drastically to 60-70% in secondary GB. As a result, reactivating p53 is suggested as a treatment strategy, either by using targeted molecules to convert the mutant p53 back to its wild type form or by using MDM2 and MDMX (also known as MDM4) inhibitors. MDM2 plays an imperative role in the down regulation of p53 activity via ubiquitin-dependent degradation and is amplified or overexpressed in 14% of GB cases. Thus, suppression of MDM2 offers an opportunity for urgently needed new therapeutic interventions for GB. Numerous small molecule MDM2 inhibitors are currently undergoing clinical evaluation, either as monotherapy or in combination with chemotherapy and/or other targeted agents. In addition, considering the significant role of both p53 and MDM2 in the downstream signaling response to radiation-induced DNA damage, the combination of MDM2 inhibitors with radiation may offer a valuable therapeutic radiosensitizing approach for GB therapy. This review covers the role of MDM2/X in cancer and more specifically in GB, followed by the rationale for the potential radiosensitizing effect of MDM2 inhibition. Finally, the current status of MDM2/X inhibition and p53 activation for the treatment of GB is given, either as monotherapy or in combination with radiation or other targeted therapies.